Monstrum z much na hagiograficznej scenie nadbałtyckich misji św. Ottona z Bambergu (przekaz Ebona z Michelsbergu o Chockowie w 1128 r. z okruchami dzieł Thietmara z Merseburga, Adama z Bremy, Helmolda z Bozowa i Wincentego Kadłubka w tle) .......... 149 - Rosik, Stanisław (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
A MONSTER OF FLIES ON THE HAGIOGRAPHIC SCENE OF THE POMERANIAN MISSIONS OF ST OTTO OF BAMBERG (EBO OF MICHELSBERG’S ACCOUNT OF GÜTZKOW IN 1128 WITH REFERENCES TO WORKS BY THIETMAR MERSEBURG, ADAM OF BREMEN, HELMOLD OF BOSAU AND WINCENTY KADLUBEK IN THE BACKGROUND) The hagiography of St Otto of Bamberg (d. 1139), traditionally known as the Apostle of Pomerania, created in the middle of the 12th century, has found a place on the literary scene for a miraculum depicting a particular type of monster, namely a swarm of flies embodying demonic powers driven out of the destroyed pagan temple at Gützkow. An analysis of this tale makes it possible to highlight, on the one hand, the functioning of animal symbolism in the Middle Ages with reference to biblical threads and, on the other hand, the sacral interpretation of the geographical space of the activities of the illustrious missionary with regard to both the sea element and Rügen (then famous as the last island of Slavic idolatry). References in this article to the works of the chroniclers mentioned in its title have proved useful in analysing this theme. They have made it possible to take a fuller look at the specificity of the sacrum of the sea in Christian symbolism, and to highlight in this context the special role of the theological interpretation of the religion of the Baltic Slavs in the discourse of the litterati of the time.